2023
DOI: 10.1111/nyas.15058
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium butyricum MIYAIRI 588 alleviates periodontal bone loss in mice with diabetes mellitus

Yanan Zhang,
Miao Lu,
Yang Zhang
et al.

Abstract: The gut microbiota is a bridge linking periodontitis and systemic diseases, such as diabetes mellitus (DM). The probiotic Clostridium butyricum MIYAIRI 588 (CBM588) is reportedly an effective therapeutic approach for gut dysbiosis. Here, in a mouse model, we explored the therapeutic effect of CBM588 on periodontal bone destruction in DM and DM‐associated periodontitis (DMP), as well as the underlying mechanism. Micro‐computed tomography revealed that DM and DMP both aggravated periodontal bone destruction, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…Calcium absorbed from food is deposited in the medullary bone, and during egg laying the calcium is reabsorbed and later deposited on the eggshell [11]. Several studies have shown the beneficial effects of CB on bone health in mice [12,13]. Tibia is an effective indicator for evaluating the bone size of poultry [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Calcium absorbed from food is deposited in the medullary bone, and during egg laying the calcium is reabsorbed and later deposited on the eggshell [11]. Several studies have shown the beneficial effects of CB on bone health in mice [12,13]. Tibia is an effective indicator for evaluating the bone size of poultry [14].…”
Section: Discussionmentioning
confidence: 99%
“…Xiang's research found that CB reduced the feed intake of Lohmann pink laying hens (180 days), improved the feed conversion ratio, eggshell strength, and albumen index, and benefitted gut health [11]. Zhan's research found that CB improved egg production and eggshell strength and benefitted the immune function and antioxidant capacity of Jinghong-1 strain laying hens (336 days) [12]. There are also studies showing that CB can reduce fat deposition in the livers of Hy-line Brown laying hens (420 days) [13] and lower the production of sandpaper-shelled eggs in Hy-line Brown laying hens (450 days) [14].…”
Section: Introductionmentioning
confidence: 99%